The Effect of Current Ratio (CR), Total Asset Turnover (TATO), Net Profit Margin (NPM), and Return on Asset (ROA) on Profit Growth in Fast-Moving Consumer Goods (FMCG) Companies Listed on the Indonesia Stock Exchange in 2017–2021 - Moh Sidqi Ramdhani; Abid Muhtarom; Titin Titin (Jurnal Ekonomi, Akuntasi dan manajemen Indonesia (JEAMI), 2024)
This study aims to analyze the effect of Current Ratio (CR), Total Asset Turnover (TATO), Net Profit Margin (NPM), and Return on Asset (ROA) on profit growth in Fast-Moving Consumer Goods (FMCG) companies listed on the Indonesia Stock Exchange from 2017 to 2021. Using a quantitative method with a Common Effect Model (CEM) panel data regression approach, this study analyzed 99 FMCG companies with a total of 419 observations. The results show that NPM (coefficient 0.623499; p=0.0014) and ROA (coefficient 2.800167; p=0.0012) have a significant and positive effect on profit growth, while CR and TATO do not have a significant effect. These findings have practical implications for FMCG company stakeholders in making profitability-ratio-based decisions to drive sustainable profit growth.